Legal regulation of the creation and activity of the Extraordinary state commission established and investigated the crimes of the german-fascist occupiers and their accomplices - Fedorchenko, Oleh; Domashova , Sofiia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The important for Ukraine issue of the aggressor’s caused damages compensation is raised in the article. Ukraine had such a bad experience. Therefore, the authors pay attention to the activity of the Extraordinary State Commission established and investigated the crimes of the German-fascist occupiers and their accomplices who caused damages to the citizens, collective farms, community organizations, State enterprises of the USSR. The purpose of the research is the legal regulation of the creation and activity of the Extraordinary State Commission. The authors have analyzed the founding documents of the Commission, which determined the main tasks of its activity: the coordination of the State organs, the complete list of the German-fascist occupiers’ committed crimes and caused damages, the identification of people committed military crimes and their bringing to trial. The principle of the formation of the Extraordinary State Commission composition is shown in the article to have been the example for all the lower commissions in republics, regions and districts. The composition of the Commission had a representative character, which purpose was propaganda. The Commissions of the lower levels were formed by the representatives of the party and executive organs, enforcement agencies and, necessarily, the Orthodox Church. The analysis of the normative and legal basis of the Commission pointed, firstly, to the non-readiness of the USSR authorities to solve such a problem and, secondly, to the prevailing the accounting of the material damages over the accounting of the victims among the population. The lawmakers’ lack of strategic thought regarding the activity of the State organ on establishing the occupiers’ crimes has been noted. No clear and simple vertical system of the State bodies having dealt with the investigation of the occupiers’ crimes and caused damages was created. In the founding documents, the role of the authorized people of the Extraordinary State Commission was not quite clearly understood, since their legal status was not determined. Management was realized manually and kept on the positions, held by the party and State organs officials and on their informal authorities as well.